Preparation of a disulfide-linked precipitative soluble support for solution-phase synthesis of trimeric oligodeoxyribonucleotide 3´-(2-chlorophenylphosphate) building blocks - Jabgunde, Amit M.; Molina, Alejandro Gimenez; Virta, Pasi; Lönnberg, Harri (Beilstein Journal of Organic Chemistry, 2015)
The preparation of a disulfide-tethered precipitative soluble support and its use for solution-phase synthesis of trimeric oligodeoxyribonucleotide 3´-(2-chlorophenylphosphate) building blocks is described. To obtain the building blocks, N-acyl protected 2´-deoxy-5´-O-(4,4´-dimethoxytrityl)ribonucleosides were phosphorylated with bis(benzotriazol-1-yl) 2-chlorophenyl phosphate. The “outdated” phosphotriester strategy, based on coupling of PV building blocks in conjunction with quantitative precipitation of the oligodeoxyribonucleotide with MeOH is applied. Subsequent release of the resulting phosphate and base-protected oligodeoxyribonucleotide trimer 3’-pTpdCBzpdGibu-5’ as its 3’-(2-chlorophenyl phosphate) was achieved by reductive cleavage of the disulfide bond.
Keywords: disulfide linker; oligodeoxyribonucleotides; phosphotriester chemistry; precipitation; soluble support